Tecendo e destecendo: as representações femininas nos contos de fadas da tradição e de Marina Colasanti - Paulino, Simone Campos (2018)
The present work, mainly bibliographic, presents a comparative study that, through the seam between the fairy tales of the tradition and those of the Italian-Brazilian author, Marina Colasanti, seeks to denounce the gender roles printed in this type of narrative and the need for a revisionism of the literary canon. In this way, the present thesis aims to approach how, taking to itself the motto of the fairy tales of the tradition, the author Marina Colasanti deconstructs the symbolic violence of the discourse of the patriarchate present in the traditional narratives. This thesis highlights the deconstruction of the fairy-tales protagonists in the Colasantian work and has as theoretical presuppositions Adichie (2017), Banditer (1985), Beauvoir (2009), Butler (2003), Coelho (1991, 2000, 2008), Colasanti (2004), Darnton (1986), Fávero (2010), Franz (1990), Martins (2006), Mendonça (2000), Michelli (2008, 2010), Oliveira (2016), Silva (1994, 2009), Tatar (2013), Todorov (2008), Vladimir Propp (2006), Warner (1999), Zipes (2006), Zolin (2007, 2009). In addition, this work presents interviews, conducted with volunteers, aiming to point to the relationship between women and fairy tales. Drawing on Anglo-Saxon feminist theory, the research draws a parallel between the feminine representations in these tales and questions the patriarchal discourse in the narratives of tradition. We also emphasize that the present thesis seeks to question the naturalization of the moral conduct of gender expressed in fairy tales and the symbolic violence that is manifested in society through the "teachings" of these narratives.